2015
DOI: 10.1002/14651858.cd006781.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Aminophylline for bradyasystolic cardiac arrest in adults

Abstract: The prehospital administration of aminophylline in bradyasystolic arrest is not associated with improved return of circulation, survival to admission or survival to hospital discharge. The benefits of aminophylline administered early in resuscitative efforts are not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Our search strategy retrieved 543 references and, after screening the titles and abstracts, nine systematic reviews (SRs) were found to fulfill our inclusion criteria and were considered for qualitative synthesis. [6][7][8][9][10][11][12][13][14]…”
Section: Search Resultsmentioning
confidence: 99%
“…Our search strategy retrieved 543 references and, after screening the titles and abstracts, nine systematic reviews (SRs) were found to fulfill our inclusion criteria and were considered for qualitative synthesis. [6][7][8][9][10][11][12][13][14]…”
Section: Search Resultsmentioning
confidence: 99%
“…Hurtley et al. ( 5 ) summarized the previous clinical trials of aminophylline use for brady-asystolic cardiac arrest; most trials use an intravenous aminophylline dose of 250 mg as the loading dose. Therefore, the authors used the same dose and started the continuous infusion (0.5 mg/kg/h), which was the recommended maintenance dose for airflow obstruction with a therapeutic theophylline level (10 to 20 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of aminophylline in atropine-resistant cardiac arrests has been considered as an accumulation of adenosine in the heart during cardiac arrest followed by cardiac ischemia which may reduce the effectiveness of catecholamines during resuscitation. Despite initial promising results ( 80 ), this hypothesis wasn’t confirmed in an independent meta-analysis ( 81 ).…”
Section: Theophyllinementioning
confidence: 97%